2007
DOI: 10.1002/jbm.b.30829
|View full text |Cite
|
Sign up to set email alerts
|

Surface micro‐analyses of long‐term worn retrieved “Osteal™” alumina ceramic total hip replacement

Abstract: We analyzed wear pattern of long-term retrieved alumina-alumina hip prostheses from Osteal, which were implanted for 15-19 years. A comparison was carried out with our previous study of 17-year Biolox alumina-on-alumina hip prostheses, (Shishido et al., J Biomed Mater Res B 2003;67:638-647) and all-alumina total hip replacement run under microseparation simulator tests. Of particular interest was the occurrence of stripe wear in these first generation alumina ceramic bearings. Two balls of Osteal revealed only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…Stripe wear on femoral heads has been a common finding in CoC retrievals [16,20,54,62,70,75,76] but rarely mentioned in the MoM literature. It is possible that bearing damage could have been produced either by THA dislocation or alternatively by instruments used at revision surgery [8,30,60].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stripe wear on femoral heads has been a common finding in CoC retrievals [16,20,54,62,70,75,76] but rarely mentioned in the MoM literature. It is possible that bearing damage could have been produced either by THA dislocation or alternatively by instruments used at revision surgery [8,30,60].…”
Section: Discussionmentioning
confidence: 99%
“…Retrieval studies of ceramic-on-ceramic (CoC) THA in particular have revealed ''normal'' wear mode produced by everyday activities as a circular wear pattern on the head and inside the cup [71,75]. There were also frequent reports of ''stripe'' wear across heads and around cup rims [15,54,62,71,77].…”
Section: Introductionmentioning
confidence: 99%
“…The stress can be mapped and linked to transformation rate. This application of Raman spectroscopy was used with retrieved zirconia femoral heads in total hip replacement [10,11]. In the dental field, it was possible to measure the compressive stress field induced at the surface after sandblasting [12].…”
Section: Quantitative Measurement Of the Residual Stress Field Storedmentioning
confidence: 99%
“…The anticipated 'normal' mode of everyday activities [20,21] created more or less circular wear patches on the head and inside the cup [22,23]. However, COC cases with 1 to 22 years follow-up also revealed evidence of a crescent-shaped type of stripe wear across femoral heads and around the rims of ceramic cups [22,[24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%